Feeding strategy trade-off and selection of marine nocturnal gastropods under predation risk - Lin, Shihui; Gao, Xiaolong; Zhang, Mo; Lyu, Mingxin; Ke, Caihuan (Frontiers in Marine Science, 2022)
The circadian rhythm is one of the most crucial and universal biological rhythms in living organisms. As a typical nocturnal creature, the Pacific abalone (Haliotis discus hannai) exhibits rhythmic behaviors in terms of passively selecting whether to avoid predators or to forage, and active adaptation to light cycle changes is regulated by the biological clock. However, no basic data are available to help us to understand these rhythmic behaviors in the abalone species. In the present study, quantification of behavioral data for the abalone and its predator swimming crab Portunus trituberculatus in short-term (24 h) and long-term (40 days) polyculture scenarios suggests that the distance and duration of movement, percentage of feeding individuals, and cumulative duration of feeding of the abalone individuals were significantly lower under the short-term predation risk than the long-term predation risk. The concentrations of 5-hydroxytryptamine (5-HT), cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), and hexokinase (HK) in hemolymph, and expression levels of 5-HT1A receptor and 5-HT2 receptor in cerebral ganglion were significantly higher under the long-term predation risk than the short-term predation risk. The concentration of lactate dehydrogenase (LDH) and glycogen content in adductor muscle of the abalone was significantly higher under the short-term predation risk than the long-term predation risk, thereby implying their role in anaerobic metabolism and aerobic metabolism as primary energy sources under the short-term and long-term predation risk, respectively. The concentrations of 5-HT and cAMP, and the expression levels of Bmal1 and 5-HT2 receptor exhibited no significant signs of cosine rhythmicity under the short-term predation risk, but changes in the movement and feeding behaviors of the abalone still occurred at the night only. Correlation analysis shows that the expression levels of Bmal1 and Clock had significantly positive correlations with the circadian changes in the movement parameters of the abalone, thereby suggesting a dominant role in the rhythmic expression of endogenous circadian clock genes regulating the rhythmic behavior of the abalone. These findings provide new insights into the origin and evolution of biological rhythms in nocturnal marine animals and a reference for developing rational stock enhancement plans, and would improve protection for marine benthic biodiversity.